Sialic acid glycoproteins inhibit in vitro and in vivo replication of rotaviruses. - Yolken, R H (1987)
We investigated the interactions of rotaviruses with glycoproteins and cells that support rotaviral replication. We found that a wide range of naturally occurring glycoproteins, including ovalbumins and ovomucoids from chicken and turkey eggs, and mucin derived from bovine submaxillary glands, inhibit the replication of rotaviruses in MA-104 cells. Our studies further indicated that the glycoproteins bind directly to rotaviruses and that virus-glycoprotein binding is dependent largely upon interactions with sialic acid oligosaccharides. We found that accessible sialic acid oligosaccharides are required for efficient rotavirus infection of MA-104 cells, thus demonstrating that sialic acid oligosaccharides play an important role in the interactions of rotaviruses with both glycoproteins and cells that support rotaviral replication. Bovine submaxillary mucin and chicken ovoinhibitor can also prevent the shedding of rotavirus antigen and the development of rotavirus gastroenteritis in a mouse model of rotavirus infection. Our findings document that a range of glycoproteins inhibit the in vivo and in vitro replication of rotaviruses and suggest that the alteration in the quantity or chemical composition of intestinal glycoproteins is a potential means for the modulation of enteric infections.